Graduating from a Conditional Cash Transfer Program in Indonesia : Results of a Household Survey of Prosperous-Independent Graduates of the Family Hope Program in 2020 - Syamsulhakim, Ekki; Khadijah, Nurzanty (World Bank, Washington, DC, 2021)
The Family Hope Program (Program Keluarga Harapan - PKH), a conditional cash transfer (CCT) program launched in 2007, has become one of the country’s flagship social protection programs, targeting the poorest families in Indonesia to reduce their expenditure burden and improve their wellbeing through education, health, and social welfare services. In the last 13 years, PKH has expanded to 10 million beneficiary families across all districts/cities in Indonesia. Studies have provided evidence of PKH’s desirable impacts, which include usage of health services, education participation, and stunting reduction (Cahyadi, et al., 2020; Alatas, 2011). However, there is still limited evidence on how families who have already left the program are doing, particularly in regard to their socio-economic status, employment and livelihood activities, program complementarities, and sustainability of the previously incentivized behavior.